TIPOLOGI BERAKHLAKUL KARIMAH DALAM MERDEKA BELAJAR - Imamul Muttaqin; Sahrul Maulana; M. Haydar Afief; Khoirun Nisaa; Fi Ramatillah Maulida; Shafira Awaliyah (Piwulang: Jurnal Pendidikan Agama Islam, 2023)
Education is the process of acquiring knowledge from educators by students. Its purpose is to enhance knowledge and shape good behavior and character. Teachers act as facilitators, while students are the main participants in the teaching and learning activities. The curriculum plays a crucial role in achieving educational goals. The "curriculum Merdeka" (independent curriculum), currently implemented in some schools in Indonesia, aims to cultivate noble character in students. Good character holds great importance in Islam, and education is the primary sector in building one's character. This research employs a descriptive research method to find solutions to problems. The strategies employed in teaching and learning activities within the independent curriculum will help shape students into exemplary Muslims, serving as role models for other Muslims.Pendidikan adalah proses mendapatkan ilmu pengetahuan dari pendidik oleh peserta didik. Tujuannya adalah menambah pengetahuan dan membentuk perilaku serta akhlak yang baik. Guru berperan sebagai fasilitator, sedangkan murid menjadi objek utama dalam kegiatan belajar mengajar. Kurikulum memiliki peran penting dalam mencapai tujuan pendidikan. Kurikulum merdeka, yang saat ini diterapkan di sebagian sekolah di Indonesia, bertujuan menumbuhkan akhlakul karimah pada siswa. Akhlak dalam Islam sangat penting, dan pendidikan menjadi sektor utama dalam membangun akhlak seseorang. Penelitian ini menggunakan metode penelitian deskriptif untuk mencari solusi dari masalah. Strategi dalam kegiatan belajar mengajar pada kurikulum merdeka akan membantu membentuk siswa menjadi pribadi muslim yang baik dan menjadi teladan bagi umat Muslim lainnya.